A integral e o cálculo de áreas. - COSTA, Elson José Monteiro (2024)
In this work we will carry out a study about the use of the integral in the calculation of areas. We will start by talking about some concepts that will later define what the Riemann integral will be. The study continues with the relation of the integral with the calculation of several areas such as the surface of revolution and in polar coordinates. Finally, we will verify that the formulas taught in basic education can be found using the Riemann integral and its properties.